(untitled) (PJDOL, 2023)
Online learning is an extension of distance learning. Online education is a new phenomenon since 1990s and increasing dramatically worldwide. E-learning offers flexibility for learning in terms of entry, course components, modes of learning and point of exit which serve the learners ‘control and choice for the content, sequence, time, place and method of learning’, including well thought assessment. There is a great deal of zealous expression about online education at every level of present dayinstitutional environment